х⁴ - 5х² - 14 = 0
х² = t.
t² - 5t - 14 = 0
D = 25 - 4 × 1 × (-14) = 81 > 0. <em><u>9</u></em><em>.</em>
х1 = ( 5 + 9 ) / 2 = 14/2 = <em><u>7</u></em><em>.</em>
х2 = ( 5 - 9 ) / 2 = -4/2 = <em><u>-</u></em><em><u>2</u></em><em>.</em>
х² = 7
х = ±√7.
х² = -2
нет корней.
<em><u>От</u></em><em><u>вет</u></em><em> </em><em>:</em><em> </em><em>-</em><em>√</em><em>7</em><em> </em><em>;</em><em> </em><em>√</em><em>7</em><em>.</em>
<em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em>
<em><u>Уда</u></em><em><u>чи</u></em><em>)</em><em>)</em><em>)</em><em>)</em>
В первом уравнении получается:
-b(1+5)
во втором:
-c(3+2)
в третьем:
15x(-1 +1)
Ответ: решение смотри на фотографии
Объяснение: